2015
DOI: 10.1016/j.conbuildmat.2015.04.057
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of Polyvinyl Butyral (PVB) at high strain rates

Abstract: h i g h l i g h t sLow-speed and high-speed direct tensile tests were performed on PVB material. Stress-strain curves were derived at strain rates from 0.008 s À1 to about 1360 s À1 . The strength was found to increase with strain rate; but PVB becomes less ductile. The testing results with available testing data were summarized and analyzed. a b s t r a c tPolyvinyl Butyral (PVB) has been largely used as an interlayer material for laminated glass to mitigate the hazard from shattered glass fragments, due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 13 publications
3
67
0
Order By: Relevance
“…Therefore, it is possible that this parameter might increase further should the material be deformed at higher rates. This further increase was also confirmed in the newer data produced by Zhang et al [11].…”
Section: −1supporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, it is possible that this parameter might increase further should the material be deformed at higher rates. This further increase was also confirmed in the newer data produced by Zhang et al [11].…”
Section: −1supporting
confidence: 77%
“…Whilst photoleasticity results showed that the strains were uniformly distributed after the very initial sample loading stage, Hooper et al [12] calculated that for the 400 s case, the rise time predicted with an assumed initial stiffness would be similar to the time taken by a stress wave to travel the length of the sample, 40 μs, prejudicing the exact stiffness measurement in the early times. Zhang et al [11] however measured longer initial yield times with a similar set up and material. This suggested the initial results were valid, as suggested here by the photoelasticity results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams-Landel-Ferry equation to shift shear modulus of different temperatures [76]. The mechanical behavior of PVB at large strain was studied at both quasi-static and dynamic states [54,[76][77][78][79][80]. Laboratory tests reveal that PVB shows viscoelastic material properties at low strain rates and is loading rate dependent.…”
Section: Pvbmentioning
confidence: 99%
“…The authors concluded that LSG panels should be designed to fail by tearing of the interlayer rather than failure at the supports to achieve a desired level of protection. Many researchers have studied the dynamic properties of glass [18,19] and PVB materials [20,21] to help design better glass resistant panels.…”
Section: Introductionmentioning
confidence: 99%